2013
DOI: 10.1093/jac/dkt405
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli belonging to the worldwide emerging epidemic clonal group O25b/ST131: risk factors and clinical implications

Abstract: Previous use of antibiotics selecting for ST131 isolates was the main modifiable risk factor for infections caused by these isolates. Our results also suggest that the clinical virulence of ST131 is not higher than that of other common E. coli causing infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 29 publications
6
53
0
Order By: Relevance
“…These studies reported similar prevalences of E. coli ST131 among the non-ESBLproducing isolates: 10% in France (2008 to 2009), 12% in Spain (2010), and 13% in each of the other two studies, carried out in the United States (2007 to 2012). However, the reported prevalence among ESBL-producing isolates was higher in the United States (49 to 50%) than in France (36%) or Spain (23%) (16,54,156,161). ESBL-producing isolates and 72% among the ESBL producers (42).…”
Section: Prevalence and Epidemiology Of E Coli St131 Among Human CLImentioning
confidence: 96%
See 4 more Smart Citations
“…These studies reported similar prevalences of E. coli ST131 among the non-ESBLproducing isolates: 10% in France (2008 to 2009), 12% in Spain (2010), and 13% in each of the other two studies, carried out in the United States (2007 to 2012). However, the reported prevalence among ESBL-producing isolates was higher in the United States (49 to 50%) than in France (36%) or Spain (23%) (16,54,156,161). ESBL-producing isolates and 72% among the ESBL producers (42).…”
Section: Prevalence and Epidemiology Of E Coli St131 Among Human CLImentioning
confidence: 96%
“…A very small number of studies (16,54) have provided information about resistance to various antibiotic families in E. coli ST131 isolates, comparing the results obtained with those for non-ST131 E. coli isolates producing or not producing ESBL (Tables 2 and 3). For ESBL-producing isolates, these studies showed that E. coli ST131 isolates were consistently more frequently resistant to amikacin than non-ST131 isolates and potentially more frequently resistant to amoxicillin-clavulanic acid, piperacillin-tazobactam, or ciprofloxacin; they were also more frequently suscep- tible to gentamicin or co-trimoxazole than non-ST131 isolates, depending on the country considered (Table 2).…”
Section: Antibiotic Resistancementioning
confidence: 99%
See 3 more Smart Citations